Work as the contemporary limit of life: Capitalism, the death drive, and the lethal fantasy of 'work–life balance'. (July 2016) - Bloom, Peter
This article introduces contemporary discourses of 'work–life balance' as a cultural fantasy revolving self-hood around employment and organizations. To do so, it draws on the Lacanian interpretation of the Freudian 'death drive' to highlight the importance of 'disequilibrium' for the construction of the subject and individual identification therein. More precisely, it reflects on the ways this structuring of self-hood associated with the impossible pursuit of 'equilibrium' maps out onto present desires for 'work–life balance' and its subsequent production of a regulated 'imbalanced' subject. It argues that individuals are maintained as subjects through their identification with and paradoxical enjoyment, or jouissance, from being 'imbalanced'. Consequently, capitalist work and organizations stand as the contemporary limit of 'life' through their fundamental role in producing and sustaining this 'imbalanced' subject in search of 'balance'. It is ironically in this longing to overcome this 'imbalance', to 'work to live', that individuals remain even more strongly a capitalist and organizational 'subject of desire'. They literally cannot go on subjectively 'living' without capitalist work.